Factors affecting skeletal integrity in an Australia Rett syndrome cohort and best practice guidelines for prevention and management of low bone density in Rett syndrome - Jefferson, Amanda Louise (Curtin University, 2016)
Rett syndrome is a rare genetic neurodevelopmental disorder. Cross sectional and longitudinal densitometry assessment in Rett syndrome found decreased bone density with age but muscle mass and mensus afforded some protection. Consensus-based clinical management guidelines provided recommendations for clinical assessment and pharmacological and non-pharmacological interventions. These data have the potential to reduce the frequency of fractures in Rett syndrome and stimulate further research that aims to ameliorate the impacts of poor bone health.